Pedagogical tact, sustainability, and edusemiotics - Gómez-Redondo, Susana; Obregón, Lilian Johanna (Frontiers in Education, 2025)
These pages provide a theoretical approach to the notion of pedagogical tact and its relation to a sustainable and transformative school from an edusemiotic approach. Pedagogical tact can be translated as the ability to generate a certain atmosphere in educational interaction. This requires sensitivity and interpretative skills. We associate the notion of tact and care with current proposals for sustainability as attention to the development of the present without compromising the needs of future generations. We propose an itinerary for educational and learning theories based on the semiotics of Charles S. Peirce and his idea of human experience as a sign to be interpreted. All this implies a relational use of the sign based on the interaction between people and their environment from positions of sustainable development. In other words, the new agenda is based on relational, integrative, empathetic, anticipatory, and systematic reflection of schools according to UNESCO.